2017
DOI: 10.3329/medtoday.v28i2.32932
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Perforation of Tympanic Membrane: A Rural Profile of Bangladesh

Abstract: To determine the various etiological factors, clinical presentation and outcome of traumatic perforation of tympanic membrane (TM) in a rural area of Bangladesh. A retrospective study of 210 cases of traumatic perforation of TM in upazilla health complex, Nangalkot and Muradnagar, Comilla, Bangladesh within the period of March 2013 to February 2014. The study showed middle age people of 20-39 years age group were mostly affected (61.89%), where males are more than females at the ratio of 1.18:1. Domestic vio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
1
2
0
Order By: Relevance
“…On left side of ear, perforation of the Tympanic membrane was observed in 39 (48.75%) patients followed by right year perforation in 32 (40%) patients while bilateral perforation was observed in only 9 (11.25%) patients. In accordance with our findings, other studies also reported left ear in majority of their cases 8,10,11 . The most likely reason for the involvement of the left side is that right-handed people often slap victims who are facing them over the left ear.…”
Section: Discussionsupporting
confidence: 93%
“…On left side of ear, perforation of the Tympanic membrane was observed in 39 (48.75%) patients followed by right year perforation in 32 (40%) patients while bilateral perforation was observed in only 9 (11.25%) patients. In accordance with our findings, other studies also reported left ear in majority of their cases 8,10,11 . The most likely reason for the involvement of the left side is that right-handed people often slap victims who are facing them over the left ear.…”
Section: Discussionsupporting
confidence: 93%
“…Majority patients were male (58%) and 42% patients were female. Similarly, 54.76% patients were male and 45.23% where female were found in the study by Mazumder and colleagues 12 . Santoshi Kumari et al found that 58.4% male and 41.4% female in their study involving patients with otitis media 13 .…”
Section: Figure 1: Clinical Presentation Of Patients (N=50)mentioning
confidence: 53%
“…The result of this study varies from Dawood’s study, where small size perforation was found in 51.5%, and posterior quadrant TM perforation found in 50% and that of Mazumder’s study where small size perforation was more common (60%) and postero-inferior quadrant was involved in 61.90% patients. 2 , 12 The probable explanation of left side involvement is that right handed person tends to slap the victim facing to him over the left ear. The air pressure change produced in the external auditory canal by slap is sufficient to cause medium size perforation in the tympanic membrane, as unveiled from the results of this study that commonest cause of perforation of tympanic membrane was slap (72.9%), while medium sized perforation was commonest perforation (56.2%).…”
Section: Discussionmentioning
confidence: 99%